(3OQGSI GdLOhi (B:s (3cja JYOgG HfaSc? (B/s - (3MejO, UdGM GdOjfs ((3GdbGgQI(B: s (3OGQ GdacQ GdYQHj(B, s, 2000)
(3jJfGhd gPG GdcJGH GdLhGfH GdeGdjI dOQGSI GdLOhi hGdJj JJdNU aj GYOGO bhGFe HGdJcGdja GdESJKeGQjI ddeTQhY Ke MSH QCS eGd GdYGed hMSGH GdJcGdja GdJfajPjI GdLGQjI GddReI dJTZjd GdeTQhY Ke MSGH QCS GdeGd GdYGe GdEgdGcGJ hGdbjeI GdeJHbjI aj fgGjI GdYeQ GdEbJUGOj ddeTQhY (B-(3GdEjQGOGJ GdLGQjIddeTQhY (B-(3MSGH eJhSWGJ GdCQHGM ddeTQhY (B-(3GYOGO HjGf jhVM GdJOabGJ GdfbOjI ddeTQhY (B-(3Jbje OQGSI GdLOhi GdeGdjI ddeTQhY (B-(3GdJMdjd GdeGdj dOQGSI GdLOhi GdeGdjI (B-(3Ke JCJj NdGUI GdOQGSI hGdJj JTed edNUG cGedG Yf GdeTQhY heG CSaQJ Yfg GdOQGSI (B-s
Keywords: (3GdJcGdjas; (3GdeTQhYGJs; (3OQGSGJ GdLOhis